2019
DOI: 10.1002/jcp.28895
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy and senescence: A new insight in selected human diseases

Abstract: Senescence and autophagy play important roles in homeostasis. Cellular senescence and autophagy commonly cause several degenerative processes, including oxidative stress, DNA damage, telomere shortening, and oncogenic stress; hence, both events are known to be interrelated. Autophagy is well known for its disruptive effect on human diseases, and it is currently proposed to have a direct effect on triggering senescence and quiescence. However, it is yet to be proven whether autophagy has a positive or negative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
84
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(85 citation statements)
references
References 59 publications
1
84
0
Order By: Relevance
“…Considering that deficient autophagy in the liver impairs the mobilization of TGs into FAs, resulting in steatosis (Singh et al., 2009) and that it could have a direct effect on triggering senescence and quiescence (Rajendran et al., 2019), we analyzed levels of proteins involved in autophagy. We found no statistically significant differences in ATG5, ATG7, or LC3 levels in 10m OPN‐KO mice (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Considering that deficient autophagy in the liver impairs the mobilization of TGs into FAs, resulting in steatosis (Singh et al., 2009) and that it could have a direct effect on triggering senescence and quiescence (Rajendran et al., 2019), we analyzed levels of proteins involved in autophagy. We found no statistically significant differences in ATG5, ATG7, or LC3 levels in 10m OPN‐KO mice (Figure C).…”
Section: Resultsmentioning
confidence: 99%
“…Under physiological conditions, autophagy can maintain the normal physiological functions of cells by eliminating damaged organelles and biomacromolecules . However, the autophagy activity of a cell is enhanced by some stresses (eg, nutritional deficiency and ischaemia) and degrades cell components and releases free amino and fatty acids, which can supplement energies, promote biomacromolecule synthesis, maintain cell survival, promote cell homeostasis, and promote adaptation to stress . Autophagy not only plays an important regulatory role in body aging and cell aging but also participates in the initiation and development of multiple geriatric diseases .…”
Section: Introductionmentioning
confidence: 99%
“…Other types of metabolic dysfunction, such as mitochondrial dysfunction, ER stress, and autophagy impairment have been implicated in senescence and discussed recently elsewhere [45][46][47][48]. Interestingly, it was found that knockdown of LSG1, a GTPase in charge of the biogenesis of the 60S ribosomal subunit, caused the perturbation of the endoplasmic reticulum homeostasis leading the cell to a senescent state [48].…”
Section: Metabolic Stressmentioning
confidence: 96%